A survey of the epibiota of Eretmochelys imbricata (Testudines: Cheloniidae) of Mona Island, Puerto Rico - Schärer, Michelle T. (Revista de Biología Tropical, 2003)
Epibiotic organisms inhabiting non-nesting hawksbill sea turtles, Eretmochelys imbricata (Linnaeus, 1766), are described from Mona and Monito Islands, Puerto Rico. Epibiont samples from 105 turtles of shallow (< 40 m) water foraging habitats were collected and identified to the lowest possible taxon. This epibiotic assemblage consisting of at least 4 algal functional groups and 12 animal phyla represents the greatest phylogenetic diversity for marine turtle epibiota. Six groups are considered new reports for marine turtles. Most epibiont colonization was found on posterior marginal scutes and under overlapping scutes. Ecological attributes of epibiota and their symbiosis with E. imbricata provide a tool to understand basi and epibiont populations.